The Effect Of Green Accounting, Environmental Performance, And Corporate Social Responsibility Disclosure On Profitability - Alinda Chandra Theana; Ni Nyoman Sri Rahayu Trisna Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Profitability is a critical factor in ensuring a company’s sustainability. In the current business environment, companies are required to balance profit with non-financial aspects, namely social and environmental considerations. This study aims to empirically examine the effect of green accounting, environmental performance, and corporate social responsibility (CSR) disclosure on profitability, using firm size as a control variable. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 246 observations. Data were analyzed using multiple linear regression techniques. The findings indicate that green accounting and firm size (as a control variable) have a significant negative effect on profitability. In contrast, environmental performance and CSR disclosure have a significant positive effect on profitability. These results imply that corporate management should strive to balance profit, social, and environmental aspects without neglecting cost efficiency. Furthermore, environmental performance and CSR disclosure can serve as key indicators in investment decision-making, as they provide favorable returns for shareholders.